ON THE RELATIONSHIP BETWEEN AREA OF UPWELLING AND POTENTIAL FISHING ZONE IN MAKASSAR STRAIT - Safruddin; Novia elvianti; Zainuddin, Mukti; Muhiddin, Amir Hamzah (Jurnal Ilmu Kelautan SPERMONDE, 2021)
This study aims to describe the relationship between the upwelling area and the ZPPI area of ​​skipjack tuna using the Generalized Additive Model (GAM) method and to map out the distribution pattern of skipjack in Barru waters, Makassar Strait. The research was conducted in November and December 2020, located in Barru waters, Makassar Strait. The research method used two methods by collecting primary data in the form of catches by following the purse seine fishing operation in Barru and secondary data in the form of satellite imagery data on sea surface temperature and chlorophyll-a. The data were analyzed using the GAM and upwelling area analysis. The upwelling area was obtained from the combination of the referred values of the two parameters. The results showed that sea surface temperature parameters had a significant effect on the catch of skipjack tuna with favored range of 28.5 - 29.7 oC.  Preferred chlorophyll-a ranged from 0.15 to 0.23 mg m-3. We found that the upwelling event in the Flores sea does not have a direct effect on the distribution pattern of skipjack tuna, there is probably a time lag required after upwelling in which in turn has an impact on the distribution of skipjack tuna in the southern Malassar Strait. Keywords: skipjack distribution, Makassar Strait, upwelling area, Flores Sea, potential fishing zone area